Surface Chemistry-Enhanced Wearable Biosensors: A Novel Approach for Non-Invasive Continuous Health Monitoring - Chen, Zhuo (International Journal of Social Sciences and Public Administration, 2024)
With the rise of health concerns in recent years, wearable biosensors have gained widespread attention as an important technology for health monitoring. It can monitor human physiological indicators such as blood glucose and lactate. This type of monitoring does not require complex operations or frequent sampling and is non-invasive and capable of real-time monitoring. Chemically modified electrochemical biosensors have further improved the sensitivity and selectivity of monitoring and have the potential for a wider range of applications. In this paper, we will explore the application of surface chemically enhanced wearable sensors for non-invasive health monitoring and their future directions.